Genetic advancements in breast cancer treatment: a review - Marzieh Shokoohi; Sadaf Sedaghatshoar; Homaira Arian; Milad Mokarami; Fatemeh Habibi; Fatemeh Bamarinejad (Discover Oncology)
Abstract Breast cancer (BC) remains a leading cause of cancer-related deaths among women globally, highlighting the urgent need for more effective and targeted therapies. Traditional treatments, including surgery, chemotherapy, and radiation, face limitations such as drug resistance, metastasis, and severe side effects. Recent advancements in gene therapy, particularly CRISPR/Cas9 technology and Oncolytic Virotherapy (OVT), are transforming the BC treatment landscape. CRISPR/Cas9 enables precise gene editing to correct mutations in oncogenes like HER2 and MYC, directly addressing tumor growth and immune evasion. Simultaneously, OVT leverages genetically engineered viruses to selectively destroy cancer cells and stimulate robust antitumor immune responses. Despite their potential, gene therapies face challenges, including off-target effects, delivery issues, and ethical concerns. Innovations in delivery systems, combination strategies, and integrating gene therapy with existing treatments offer promising solutions to overcome these barriers. Personalized medicine, guided by genomic profiling, further enhances treatment precision by identifying patient-specific mutations, such as BRCA1 and BRCA2, allowing for more tailored and effective interventions. As research progresses, the constructive interaction between gene therapy, immunotherapy, and traditional approaches is paving the way for groundbreaking advancements in BC care. Continued collaboration between researchers and clinicians is essential to translate these innovations into clinical practice, ultimately improving BC patients' survival rates and quality of life.